Systematic review: MRI enterography for assessment of small bowel involvement in paediatric Crohn's disease. Issue 12 (3rd May 2013) - Giles, E.; Barclay, A. R.; Chippington, S.; Wilson, D. C.
Summary Background Barium meal enteroclysis (BM) is the recommended imaging technique for small bowel inaccessible by ileo‐colonoscopy when diagnosing paediatric‐onset inflammatory bowel disease, but it has poor sensitivity and involves ionising radiation. MRI enterography (MRE) is an alternative methodology. Aims To critically appraise the published evidence on MRE in the assessment of Paediatric inflammatory bowel disease by systematic review. Methods Review of all English language data reporting MRE for the investigation of patients <18 years with known or suspected IBD. Primary searches of Medline (Jan 1950–April 2012), Cinahl (1966–April 2012) and Pubmed (Jan 1950–April 2012) were performed using keyword and MeSH terms; IBD; Magnetic resonance imaging; small bowel imaging; EMBASE was then searched. Two authors independently assessed the quality of studies using the quality assessment of diagnostic accuracy studies tool. Results Searches yielded 930 035 hits, combination word searches limited to 1983 titles. Fifty‐two studies were fully reviewed, 41 were excluded due to lack of paediatric data. Eleven studies of 496 children were included. All studies used endoscopy as the reference test. 10/496 patients required jejunal intubation for bowel preparation. Meta‐analysis of six comparable studies gave a pooled sensitivity and specificity for MRE detection of active terminal ileal Crohn's disease of 84% and 97% respectively. Studies displayed heterogeneity in bowel preparation, scanning technique, reporting methodology and timing of ileo‐colonoscopy in relation to MRE. In three studies comparing BM, MRE had greater sensitivity and specificity. Conclusions MRE is a sensitive and specific tool for diagnosis in paediatric inflammatory bowel disease. Technical considerations require refinement and standardisation; however, MRE has no radiation. Current data suggest that MRE should supersede BM as the SB imaging technique in centres with appropriate expertise.